Taḥlīl Muḥtawá al-Kitāb al-Madrasī lil-Lughah al-ʿArabīyah li-Ṣaff al-Sābiʿ li-Ḥasan Sayf Allāh bi-Madkhal Mutaʿaddid al-Wasa’iṭ - Siti Sanah; Muhammad Ibnu Pamungkas; Vanessa Aulia (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2025)
This study analyzes the Arabic language textbook for seventh grade authored by Hasan Saefulloh through a multimodal approach. This study is grounded in the recognition that textbooks continue to serve as one of the principal media for language instruction, yet their visual and textual integration is often less than optimal. The study employs a qualitative content analysis method using systemic functional linguistics (SFL) and multimodal discourse analysis by Kress and van Leeuwen. Data were drawn from selected pages of the textbook that contain prominent multimodal elements, including vocabulary lists, dialogues, illustrations, and page layouts. The findings reveal three major points. First, the book presents basic Arabic learning materials but the integration between texts, images, and layouts is still weak. Second, the multimodal elements often work in isolation without forming a cohesive meaning. Third, the lack of balance between visual and verbal representations may limit students’ comprehension and engagement. This research concludes that the textbook needs improvement in its design and organization, particularly in aligning verbal and visual modes to support effective Arabic learning. This study contributes to the enhancement of multimodal awareness in Arabic textbook design, offering insights for teachers, authors, and curriculum developers to produce more pedagogically integrated materials.